Physical fitness and shooting accuracy: an evaluative study on early adolescent archery athletes - Rahmaniar Wahyuningtias; Indra Himawan Susanto; Ananda Perwira Bakti; Soni Sulistyarto (Sriwijaya Journal of Sport, 2025)
Research Problem: Accuracy in archery is a crucial aspect that must be supported by optimal physical fitness to achieve consistent shooting performance. Research Objective: This study aims to evaluate the components of physical fitness and examine their relationship with shooting accuracy among U13 archery athletes. Methods: This research employed a quantitative descriptive design with a cross-sectional approach. The sampling technique used was total sampling, involving 20 athletes from the Fast Archery Club. Data were collected through a series of physical fitness tests, including the Stork Stand, Wall Toss Test, Hand Grip, Push-Up, and Beep Test, along with shooting accuracy assessments. Data analysis was performed using multiple linear regression to determine the relationship between physical fitness components and shooting accuracy. Results: The findings indicate that the physical fitness level of U13 archery athletes was mostly in the “sufficient” category (45%), while the average shooting accuracy score was 506.6. The correlation coefficient between physical fitness and shooting accuracy was r = 0.516 (p > 0.05), indicating a moderate but statistically nonsignificant relationship. Conclusion: There is a moderate relationship between physical fitness and shooting accuracy, although the correlation is not statistically significant (p > 0.05). Despite the sufficient level of physical fitness, it is necessary to implement specialized training programs focusing on improving shooting accuracy to optimize athlete performance. Future research is recommended to explore technical and psychological factors that may influence shooting accuracy.